Recent advances in MRI technology: Implications for image quality and patient safety - Sobol, Wlad T. (Elsevier, 2012)
Recent advances in MRI technology are presented, with emphasis on how this new technology impacts clinical operations (better image quality, faster exam times, and improved throughput). In addition, implications for patient safety are discussed with emphasis on the risk of patient injury due to either high local specific absorption rate (SAR) or large cumulative energy doses delivered during long exam times. Patient comfort issues are examined as well.